An experimentally determined field winding model with frequency‐dependent parameters - Roberto Felicetti; Curt Johan David Abrahamsson; Urban Lundin (IET Electric Power Applications, 2021)
Abstract Herein, a set of experimental procedures is presented for determining the main electrical distributed parameters of the field winding in salient pole synchronous machines. It applies to the electrical characterisation of iron‐core power inductors and transformer windings as well, in a range of frequency useful for power electronics applications. A first estimation of the parameters is obtained by forcing the winding into resonance with capacitors of known capacitance. The obtained estimates are then refined through an iterative process, which makes use of the winding natural frequencies. The presented procedures are applied step‐by‐step to the field winding of a 60‐kVA salient pole synchronous generator with solid poles. The distributed parameters model, featured using the outlined procedures, accurately reproduces the winding voltage distribution in a large range of frequency. Finally, it is explored how the interaction between armature and rotor influences the field winding parameters, pointing to the differences of measuring them with the rotor inside or outside the machine bore.